UJI PENDAHULUAN KLON-KLON BAWANG MERAH ( Allium ascollonicum L.) First screening at shallot clones (Allium ascollonicum L.) - Putrasamedja, Sartono (Jenderal Soedirman University, 2010)
UJI PENDAHULUAN KLON-KLON BAWANG MERAH ( Allium ascollonicum L.)First screening at shallot clones (Allium ascollonicum L.)Â ABSTRACT.Research was canducted same information candidat superior some clone from hibriditation theexperimental, experiment was carried out at experimental garden of districk farmer Kramat-Tegal, Central Java(6 m masl) from April to June 2007. The experiment was arranged. Randomised Block Design (R.B.D) with thosereplication. Clones to experiment contain 13 treatmen, clone 2, clone, clone3, clone5, clone6, clone7, clone11,clone12, clone21,clone24, local cultivity of Bauji, Bima Brebes and Phillipina to control. The result that clone 4to hights potential of product 18,446 ton/Ha, clone 7, clone 11 and clone 21 haved average of bulp diameter2,5cm and clone 3 haves 6 of sprout.Key words: cultivar, first of screening, clone, hibriditation.